Micromorphic constitutive equations with damage applied to metal forming. (March 2017) - Diamantopoulou, Evangelia; Liu, Weijie; Labergere, Carl; Badreddine, Houssem; Saanouni, Khemais; Hu, Ping
The micromorphic constitutive model developed in previous works and accounting for isotropic plasticity, mixed kinematic and isotropic hardening and micromorphic damage is revised in order to enhance some coupling aspects. The associated numerical aspects are investigated and implemented into ABAQUS®/Explicit solver by developing two subroutines VUMAT to implement the micromorphic model and VUEL to implement an assumed strain-based element with additional micromorphic degrees of freedom. The tensional and bending tests of DP1000 dual phase steel are simulated and used to validate the model by comparing with experimental results.